Factores causales de la deserción estudiantil en el pregrado de la facultad de odontología de la Universidad de Antioquia de 1997 a 2004 (2007)
ABSTRACT: Student desertion is the definitive abandonment of the classroom by different reasons and the non continuance of the academic program. There are different determining factors. These could be intrinsic, that is, belonging to the student, or extrinsic when they don’t depend on the student. Methods: this is retrospective, descriptive educational study with a qualitative - quantitative analysis that allows the determination of causal factors of student desertion in the School of Dentistry of the University of Antioquia. Of the 71 deserting in the period 1997-1 through 2004-1, only 50 answered the survey, 16 who reentered the program and 34 that deserted these were the two groups analyzed. A different survey was presented to each group in order to find the intrinsic and extrinsic factors, the social-cultural and demographic variables that might have influenced the desertion. The results of this survey were complemented for analyses with focus groups. Results: student desertion in the school is a phenomenon that has been slowly increasing during the past 10 years, with the highest peak in year 2001 (18.1% deserters, and 35.7% for reentering students). The highest desertion appeared in the fourth semester, (29.4% for deserters, and 31.3% for reentering students), this can be attributed according to the analysis with focal groups, to the initiation of clinical practice, where they confront their fears and have greater management and responsibility problems with patients. Conclusions: among the extrinsic factors in desertion in order according to relevance are: financial factors, work, academic load, poor methodology and sexual harassment. Among the intrinsic factors is noticeable the change of academic programs due to lack of motivation, and lack of time. It is suggested that Institutions of Higher Education offer a more flexible curricula specially in the scheduling in order to decrease student desertion.